2019
DOI: 10.3390/ma12172713
|View full text |Cite
|
Sign up to set email alerts
|

Printed Flexible Microelectrode for Application of Nanosecond Pulsed Electric Fields on Cells

Abstract: Medical treatment is increasingly benefiting from biomedical microsystems, especially the trending telemedical application. A promising modality for tumor therapy showed the application of nanosecond pulsed electric fields (nsPEF) on cells to achieve nanoporation, cell death, and other cell reactions. A key technology for this method is the generation of pulsed fields in the nanosecond range with high-field strengths in the range of several kilovolts per centimeter. For further biomedical applications, state-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…After applying voltage of 100 kV cm −1 and 45 ns pulse duration, they found that the cell contracted, detached from the electrode, and almost died. [ 63 ]…”
Section: Electronics Fabricated By E‐jet Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying voltage of 100 kV cm −1 and 45 ns pulse duration, they found that the cell contracted, detached from the electrode, and almost died. [ 63 ]…”
Section: Electronics Fabricated By E‐jet Printingmentioning
confidence: 99%
“…After applying voltage of 100 kV cm −1 and 45 ns pulse duration, they found that the cell contracted, detached from the electrode, and almost died. [63] Besides metal NPs, carbon materials are also used for the fabrication of the electrodes by e-jet printing.…”
Section: Electrodes Of Metal Npsmentioning
confidence: 99%
“…In recent years, the AC electric field has been introduced into the EDW process for the fabrication of precise micro/nano structures [11,12]. The AC electric field can reduce the accumulation of the charges on the nozzle by neutralizing the electric polarity, which can help to suppress the charge repulsion interferences under the DC electric field and promote jet stability and deposition precision [13][14][15]. Under the AC electric field, the free charges reciprocate along the jet and the polarity of the electric field force on the jet changes periodically, then micro/nano droplets can be obtained at a corresponding frequency [16,17].…”
Section: Introductionmentioning
confidence: 99%